2004
DOI: 10.1097/01.ccm.0000139691.54108.1f
|View full text |Cite
|
Sign up to set email alerts
|

Effect of long-term and high-dose antithrombin supplementation on coagulation and fibrinolysis in patients with severe sepsis*

Abstract: In this first study on long-term antithrombin therapy, antithrombin significantly reduced septic coagulatory response in patients with severe sepsis when given over 14 days.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
35
0
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(40 citation statements)
references
References 40 publications
3
35
0
2
Order By: Relevance
“…In these studies, significant improvement of coagulation and fibrinolytic markers following antithrombin administration was noticed; however, antithrombin had no effect on the course of platelet counts over time [4,12,19]. In the present study, we observed a significant increase in the platelet counts and fibrinogen levels in responders.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…In these studies, significant improvement of coagulation and fibrinolytic markers following antithrombin administration was noticed; however, antithrombin had no effect on the course of platelet counts over time [4,12,19]. In the present study, we observed a significant increase in the platelet counts and fibrinogen levels in responders.…”
Section: Discussionsupporting
confidence: 70%
“…Several studies reported an effect of antithrombin administration on hemostatic variables in critically ill patients [4,12,29]. In these studies, significant improvement of coagulation and fibrinolytic markers following antithrombin administration was noticed; however, antithrombin had no effect on the course of platelet counts over time [4,12,19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Four-day antithrombin therapy did not attenuate hypercoagulability measured according to the platelet counts and global markers of coagulation and thromboelastography in patients with sepsis [28]. Hoffmann et al [29] indicated that long-term and high-dose antithrombin supplementation reduces septic coagulatory responses in patients with severe sepsis when given over 14 days. In their study, the antithrombin effects on platelet counts and markers of coagulation and fibrinolysis became evident after one week of therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Unter dieser individualisierten Substitution normalisierten sich die globalen Gerinnungstests; es erhöhten sich die Faktor-II-Aktivität, die Konzentrationen von Fibrinogen, Präkallikrein und Protein C. Antithrombin hatte keinen Einfluss auf C1-Esterase-Inhibitor (C1-INH), Plasminogen, α 2 -Antiplasmin und Plättchenzahl. Die Kontrollgruppe zeigte hingegen keine Veränderung der Parameter [13]. …”
Section: Weitere Datenunclassified